2008
DOI: 10.1590/s1516-635x2008000400007
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of sunflower meal, with or without enzyme supplementation, in broiler diets

Abstract: Two experiments were carried out to evaluate the effects of the dietary inclusion of different dietary sunflower meal (SFM) levels (0% and 20%), with or without the supplementation of an enzyme complex (EC) (cellulase, β-glucanase, xylanase, and phytase) on broiler performance, carcass and cuts yields, economics, and dietary AMEn values. A randomized block experimental design, with a 2x2 factorial arrangement of eight replicates of 20 birds each, was used to test performance. A completely randomized exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 4 publications
6
23
1
1
Order By: Relevance
“…Similar results were obtained by Oliveira et al (2003) and Tavernari et al (2008), who used 0 and 20% and 0, 15 and 30% sunflower meal, respectively. Based on performance results, Furlan et al (2001) verified that it is possible to replace up to 30% of soybean meal protein by sunflower meal protein, depending on the market price of sunflower meal at the time of utilization.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were obtained by Oliveira et al (2003) and Tavernari et al (2008), who used 0 and 20% and 0, 15 and 30% sunflower meal, respectively. Based on performance results, Furlan et al (2001) verified that it is possible to replace up to 30% of soybean meal protein by sunflower meal protein, depending on the market price of sunflower meal at the time of utilization.…”
Section: Resultssupporting
confidence: 90%
“…Tavernari et al (2008), using 0 and 20% sunflower meal, concluded that, during the starter and entire experimental phases, feed intake was significantly lower when sunflower meal was used, which may be explained by the high crude fiber and vegetable oil dietary content; however, there was no significant effect on weight gain. Pinheiro et al (2002) observed that the inclusion of 12% sunflower meal in broiler diet did not affect live performance, and that the best economic performance between three and 35 days was obtained when no sunflower meal was included in the diet, and from 36 to 42 days of age, with 4% sunflower meal dietary inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, Sherif et al (22) observed no beneficial impacts for enzyme supplementation on protein efficiency ratio. Poultry and monogastric animals do not have an endogenous capacity to digest fiber, and therefore the use of exogenous enzymes is important as they hydrolyze nonstarch polysaccharides that can potentially be used by the animals, improving, for instance, energy use (23).…”
Section: Protein and Energy Efficiency Ratios Results Inmentioning
confidence: 99%
“…Concerning the fiber for broilers, the physical density of the diet can change depending on the fiber content in the diets; the feed intake is decreased due to the high volume that fiber occupies in the digestive tract, which can also interfere with the water retention capacity (SUNDU; KUMAR;DINGLE, 2006). A similar linear decrease in feed intake with increasing SFM levels was reported by Tavernari et al (2008) who tested 0 to 20% SFM dietary inclusion in birds from 1 to 21 d of age. However, in contrast to the current study, Tavernari et al, (2008) reported a positive effect in feed conversion ratio at all growth phases.…”
Section: Resultsmentioning
confidence: 60%